The Role of Foreign Trade in Economic Development - الفيتوري, عطي (Dirasat in Economics and Business, 1980)
The purpose of this paper is to investigate the role of foreign trade in economic development, both in a typical developing economy and in the special case of the Libyan economy. The many studies in the economic literature which investigated the relationship between foreign trade and economic development, showed significant importance of this relation. A typical developing economy will need to import more goods and commodities, so economic development can take place, that is because of the need to satisfy the increasing demand for consumer goods on one hand and the need to transfer savings into investment, so machinery and other capital good have to be imported. As the development process takes place the structure of the economy will change and that will be reflected on the pattern of trade. the structure of its foreign trade to the spending policy which aims at a fair income distribution, so part of the oil revenues is distributed through public spending on housing, schools, health, and others which in overall will accelerate the growth of the services sector.